Film Dokumenter Sebagai Metode Alternatif Penelitian Komunikasi - Rocky Prasetyo Jati (Avant Garde, 2021)
The use of audio-visual media as a documentation tool in research practice is growing along with technology development. Audio-visual media has advantages and benefits in searching for audio-visual data such as depth of information. This development is a new opportunity for research method innovation. This article argues that documentary films as an embodiment of audio-visual media are an alternative method in research practice. Documentary films are used as research tools, data/information, or research dissemination facilities and can be considered research methods. The use of digital media technology in making documentary films is also a concern of this article because it makes it easier for researchers, primarily to fulfill the functions of supporting tools for research data retrieval and data analysis. While documentary filmmaking has long been seen as a creative endeavor, it is now finding an opportunity in academia. However, some questions remain about the characteristics of documentary filmmaking as a research approach. This article attempts to show the methodological process adopted by documentary films as a qualitative research strategy. This study uses a qualitative approach with the method of literature study and observation and observation of two documentary film productions based on community research. This article will describe: 1) the documentary film approach as an alternative method in research practice; 2) stages of making a documentary film relevant to the need for data collection and analysis. The results of this study reveal that the use of documentary films as an alternative method of research offers creative and innovative ideas in research outcomes and supports research results that are rich, in-depth, dynamic, in sharing knowledge.